Monetary transmission in Germany: new perspectives on financial constraints and investment spending - Ulf Von Kalckreuth (European Central Bank (ECB), 2001)
In order to obtain a better understanding of the transmission channels for monetary policy, this paper assesses the importance of the interest rate and credit channels on business fixed investment in Germany. Our unbalanced panel of financial statements contains 44,345 firm/year observations for 6,408 firms. We uncover a rather solid interest channel. A transitory increase in nominal interest rates by 100 basis points would depress investment demand by almost 4% within the first year. Using our direct measure of creditworthiness, we can also document a balance-sheet channel. Relative to unconstrained firms, financially constrained firms exhibit increased sensitivity to internal funds, and decreased sensitivity to the user cost as well as to market demand. Furthermore, changes in the rating of firms seem to affect investment demand in a way that is consistent with the presence of a balance-sheet channel. This balance-sheet channel, however, seems to be of secondary importance
Keywords: E5; E2; 330; finance; firm investment; monetary transmission; user cost